2012
DOI: 10.1111/jph.12006
|View full text |Cite
|
Sign up to set email alerts
|

Strobilurins Seed Treatment Enhances Resistance of Common Bean Against Bean common mosaic virus

Abstract: Commercial formulations of strobilurins (azoxystrobin, kresoxim-methyl, trifloxystrobin and pyraclostrobin) were evaluated for their efficacy against Bean common mosaic virus (BCMV) in screenhouse and field conditions. Highest seed germination and seedling vigour were recorded with 20 lg/ml pyraclostrobin seed treatment in comparison with the control. In screenhouse studies, 76% protection against BCMV was recorded with pyraclostrobin seed treatment at 10 lg/ ml. Under field conditions with natural BCMV inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Alternatively, identification of endophytes with tolerance to the applied fungicide and possessing the positive traits of the sensitive endophytes could allow seed treatments to be continued without impairment of the endophyte-induced functions ( Murphy et al, 2017 ; Shen et al, 2019 ). The use of reduced-risk fungicide with narrower activity and targeted against specific pathogens could also alleviate the problems imposed by broad spectrum conventional fungicides ( Adaskaveg et al, 2005 ; Udayashankar et al, 2012 ). The consequences of seed treatment with fungicides could also vary among plant species.…”
Section: Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, identification of endophytes with tolerance to the applied fungicide and possessing the positive traits of the sensitive endophytes could allow seed treatments to be continued without impairment of the endophyte-induced functions ( Murphy et al, 2017 ; Shen et al, 2019 ). The use of reduced-risk fungicide with narrower activity and targeted against specific pathogens could also alleviate the problems imposed by broad spectrum conventional fungicides ( Adaskaveg et al, 2005 ; Udayashankar et al, 2012 ). The consequences of seed treatment with fungicides could also vary among plant species.…”
Section: Research Gapsmentioning
confidence: 99%
“…In many countries including the United States, Australia and France, pre-sowing fungicidal treatment of field crops is a routine practice ( White and Hoppin, 2004 ; Agreste, 2019 ; Lamichhane et al, 2020 ; You et al, 2020 ). However, in these countries, there has been an increasing emphasis on the use of reduced-risk fungicides which have a high specificity for target organisms ( Adaskaveg et al, 2005 ; Udayashankar et al, 2012 ). In India, the annual consumption of MBC fungicide is more than 2,000 metric tons ( Singh et al, 2016 ) and it is registered for use in 18 crops including apple, bean, brinjal, barley, mango, cucurbit, cotton, grape, groundnut, jute, pea, paddy, rose, sugar beet, wheat, walnut and tapioca ( Bhushan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This fungicide is also well known for its plant health effects so that it can be used as a plant growth regulator . Field studies showed that foliar application of pyraclostrobin can significantly increase the yield of many crops including soybean. , In addition, pyraclostrobin can also activate the plant immunity system, leading to increased defense against pathogen infections. , Recently, pyraclostrobin has been used as a common foliar fungicide in soybean fields for the control of rust, anthracnose, or other plant diseases. , To date, pyraclostrobin has not been registered for soybean seed treatment in China. Therefore, it is important to evaluate the use of pyraclostrobin in soybean seed treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals that alter plant physiology have been studied as a new strategy to control plant diseases because they activate defense mechanisms that reduce the disease incidence in different pathosystems (Udayashankar et al, 2012;Guimarães et al, 2014;Itako et al, 2015;Skandalis et al, 2016). However, little information is available on how these chemicals induce the resistance mechanisms that lead to control of viruses in tomato plants.…”
Section: Introductionmentioning
confidence: 99%